Peripheral stent technology and current status for endovascular treatment of femoropopliteal artery disease: a clinical review - Dave, Bhargav; Shah, Rikin (International Journal of Research in Medical Sciences, 2018)
Over the past decade, the treatment of peripheral artery disease poses a number of technical challenges for the physician. The primary rationale of this article is to review the available literature on the current practices involved in the treatment of peripheral artery disease (PAD), particularly the femoropopliteal lesions. It is evident from the landmark clinical trials that the use of self-expanding drug-eluting stents (DES) has become the most favored clinical strategy for treating peripheral lesions above the knee. It is chiefly due to higher patency rates, and minimal in-stent restenosis and stent fracture rates associated with the use of DES. The technical evolution in the endovascular approach from the use of bare nitinol stents to DES for treating PAD and the factors responsible for this transformation have also been reviewed with their respective justification. Presently there is a need of DES technology for the treatment of femoropopliteal lesions, which can reduce the risk of stent fracture and in-stent restenosis for longer lesions while maintaining patency during long-term follow-up. To conclude, this review establishes that self-expanding DES and drug coated balloons using anti-proliferative drugs like sirolimus and paclitaxel are currently the most effective method of treating the femoropopliteal lesions in PAD.